Teachers’ Practices of Reflective Teaching in EFL Classroom - Nabila Widiastari; Rahmah Fithriani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Reflective teaching (RT) is a strategy to improve student learning outcomes. Teachers have recently used reflective teaching extensively to enhance learning and teaching outcomes. This research presents teacher practices for implementing reflective learning in English as a Foreign Language (EFL) classes. This research explores teachers' reflective practices, their methods, and the outcomes resulting from these practices. Method: The research method used is a qualitative study using questionnaires for data collection and in-depth interviews with several EFL teachers. Results: The results showed variations in reflective practice, with some teachers using student feedback, video recordings, diaries, group discussions, and self-observation as reflection methods. This research also found that reflective practice can improve teachers' understanding and skills in teaching EFL. Novelty: The novelty of this research lies in revealing specific reflective practices that can improve the quality of learning English as a foreign language.